THE EFFECTIVENESS OF REGIONAL REGULATION NO. 6/2012 ON WASTE MANAGEMENT AND RETRIBUTION FOR DISPOSAL OR SANITATION SERVICES - Ambarsari, Linda Ariska; Sushanty, Vera Rimbawani (jfpublisher, 2024)
The issue of waste management in Indonesia is a persistent environmental issue. Waste is any unwanted material from human activities. Waste management means planned, comprehensive, and sustainable activities that include waste reduction and management. This research aims to examine the effectiveness of implementing Sidoarjo Regional Regulation No. 6/2012 on Waste Management. The research method used is the empirical method, which analyzes the law based on community behavior using field data, interviews, and observations. The results indicated that the implementation of Sidoarjo Regional Regulation No. 6/2012 on Waste Management has not been effective because some elements in the theory of legal effectiveness have not been complied with, such as minimal public understanding of the regulations, suboptimal law enforcement, inadequate facilities and infrastructure, relatively low public awareness, and cultural factors.